A role of human beta defensin‐1 in predicting prostatic adenocarcinoma in cases of false‐negative biopsy. Issue 12 (8th September 2017) - Hong, Soon Auck; Kim, Ki Hong; Lee, Tae Jin; Park, Eon Sub; Kim, Mi Kyung; Myung, Soon Chul
Abstract : The purpose of this study was to clarify the role of human beta defensin‐1 (hBD‐1) in predicting PAC in morphologically normal prostate glands. In total, 25 patients with a negative initial biopsy for PAC and diagnosed as PAC positive in subsequent biopsies performed within 1 year of the initial biopsy were included. As a control group, 22 patients negative for PAC in at least three consecutive histologic examinations were selected. Expression of hBD‐1 was analyzed separately via immunohistochemistry in paired cores of non‐neoplastic gland and PAC in the false‐negative group and control group. Loss of hBD‐1 expression was observed in 95.6% and 90.0% PAC cases with Gleason Patterns 3 and 4 in repeat biopsies, respectively. hBD‐1 loss of basal cells in 40 (85.1%) previous non‐neoplastic biopsy cores in the false‐negative group was observed, in contrast to preserved basal cell expression of hBD‐1 in 64 (72.7%) biopsy cores in the control group (p = 0.001). Multivariate logistic regression analysis showed that hBD‐1 basal cell loss (≥20% of prostatic glands in total cores) is an independent factor for predicting PAC (odds ratio: 4.739, confidence interval: 1.093–20.554, p = 0.038). hBD‐1 loss of basal cells is a useful indicator to identify extremely high‐risk patients with initially negative biopsy.